The Body Matters - Alexiev, Mladen; Panayotov, Stanimir (Identities: Journal for Politics, Gender and Culture, 2011)
Author(s): Mladen Alexiev Title (English): The Body Matters Translated by (Bulgarian to English): Stanimir Panayotov Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 1 (Winter 2011) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 89-95 Page Count: 7 Citation (English): Mladen Alexiev, “The Body Matters,” translated from the Bulgarian by Stanimir Panayotov, Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 1 (Winter 2011): 89-95.